Marriage as an argument for energy poverty reduction: The moderating role of financial inclusion - Simplice Asongu; Amarachi O. Ogbonna; Mariette C. N. Mete (African Governance and Development Institute (AGDI), 2024)
The present research extends the extant literature by investigating the hypothesis on whether marriage can be a substitute for financial inclusion in energy poverty reduction in Ghana. Pooled data and two stage least squares techniques are used in the estimation process and the validity of the tested hypothesis (i.e., that marriage is a substitute for financial inclusion in energy poverty mitigation) is based on two main criteria: (i) a positive interactive effect relative to the negative unconditional effect of marriage; (ii) a marriage net effect lower in magnitude compared to the unconditional effect of marriage and (iii) an insignificant interactive effect when both unconditional effects are negative. The investigated hypothesis is not valid in the full sample, urban sub-sample and female sub-sample while it is valid in the rural and male sub-samples. Policy implications are discussed.
Keywords: D03; D12; D14; I32; Q41; 330; Energy poverty; financial inclusion; consumption poverty; education; household income